Mobilizing precarious workers in Italy: two pathways of collective action intentions. (3rd September 2022) - Politi, E.; Piccitto, G.; Cini, L.; Béal, A.; Staerklé, C.
ABSTRACT: Following increased flexibilization of labour market and related decline of traditional labour unionism over the last few decades, studying mobilization processes of precarious workers has become particularly timely. While localized forms of organization and unionization are gradually emerging, little is known about why workers intend to join these coordinated forms of collective action. Integrating social movement studies with social psychological literature on collective action, this study fills this gap by exploring collective action intentions in the current context of non-standard labour. To do so, we surveyed precarious workers enrolled by temporary hiring agencies in Italy ( N = 379) and found two parallel psychological pathways explaining their collective action intentions. On the one hand, participants exhibited high collective action intentions when they were able to collectively identify with other precarious workers as part of the same social group. Collective identification with precarious workers increased group-based injustice that in turn predicted collective action intentions. On the other hand, participants also exhibited high collective action intentions when they were able to politically identify with unionized workers. Politicized identification with unionized workers increased collective efficacy that in turn predicted collective action intentions. By singling out the complementary role played by these two parallel pathways of collective action intentions among precarious workers, this study shed light on the socio-psychological determinants underlying the mobilization propensity of individuals still lacking any organizational affiliation, a topic that has been relatively ignored in scholarly literature. In doing so, we combine social movement studies and social psychological literature in innovative ways.